The Effect of The Pandemic on Public Relations DIY Tourism: SWOT Review - Awaloedin, Dipa Teruna; Pradini, Gagih; Ramdani, Apri; Andini, Davi Ayu (CV ODIS, 2024)
This study evaluates the crisis in the DIY tourism industry due to the COVID-19 pandemic, with a focus on the crisis management and communication strategies adopted by the DIY Tourism Office. Through SWOT analysis, the research identifies strengths, weaknesses, opportunities, and threats influencing the adjustment and recovery of DIY tourism. The findings underscore the need for enhancing human resources competence, integrated marketing, and cross-sector collaboration. The study aims to provide insights for the DIY Tourism Office and other stakeholders in crisis management and strengthening the DIY tourism industry.